Assessing a sexual history during intake: a preliminary study with licensed professional counselors. Issue 4 (1st October 2020) - Gregory, Adam; Paylo, Matthew J.
Abstract: Prior research has shown an increase in individuals living with and suffering from sexual dysfunctions and other sexual-related disorders. A sample of 939 Licensed Professional Counselors (LPC) completed a 30-item questionnaire evaluating the importance, comfort, and actual practice of assessing for a thorough sexual history during an intake session. Results suggest that implementing a thorough sexual history assessment during intakes is warranted. However, many respondents expressed varying levels of discomfort initiating and engaging in these types of discussions with clients. In addition, many respondents reported avoiding the actual practice of initiating a thorough sexual history citing feeling ill-prepared due to counseling programs' lack of training and preparation.